Study of Hegu Point Stimulation in Increasing Toddler's Appetite as a Complementary Local Wisdom Therapy - Patemah, Patemah; Rufaindah, Ervin (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2025)
Toddlers require a balanced diet for their growth and development. Child growth and development can be disrupted if a child experiences stunting due to unmet food needs. To meet food needs, it is necessary to increase the toddler's appetite. To increase appetite, one alternative is to provide stimulation. The research aims to provide Hegu point stimulation to increase appetite in toddlers. This research used a descriptive method with 15 toddler participants. The population of this study consisted of toddlers aged 13 months to 60 months. Sampling technique with total sampling. The participants will have their appetite measured before and after being given Hegu stimulation. Stimulation was given once a day with 30 rounds for 30 days. The results showed that the number of female toddlers was 8 (53 percent), and the number of male toddlers was 7 (47 percent). The increase in appetite was observed in 8 toddlers (53percent) and more than twice as many toddlers (7, 47 percent). Thus, there is an increase in toddlers' appetite after giving Hegu stimulation, so that in future research, the duration of stimulation can be considered.